Walnut Meal as Feed Additive in Broilers Nutrition: Effects on Performance and Thigh Meat Quality - Arabela Elena Untea; Tatiana Dumitra Panaite; Filip Iliescu; Raluca Paula Turcu; Petru Alexandru Vlaicu (Scientific Papers Animal Science and Biotechnologies)
The aim of the study was to evaluate the effect of dietary walnut meal inclusion on productive parameters of broiler chickens’ and thigh meat quality. A nutritional trial was conducted on 80 Ross 308 broilers, raised in semi-intensive system conditions, reared on permanent shave litter (10–12 cm thick) in boxes of 3 m2 (40 broilers / each group, housed in a single box), fed ad libitum, having free access to the water. The diets given to the broilers, consisted of a control diet (C group) and an experimental diet with 6% walnut meal (E group). During the experimental period, production performances were recorded. At 42 days of age, 6 birds from each group were slaughtered and thigh meat samples were collected. The results showed that walnut meal supplement negatively influenced the final body weight, when compared with C group. Regarding the proximate composition of thigh meat, a decrease of crude fat concentrations was registered at the end of experiment (12.66 vs 10.49%) but also a significant improvement of quality of lipids in terms of omega 3 concentrations and omega 6 to omega 3 ratio (2.22 vs 2.90% omega 3 and 3.28 vs 2.66 omega6/omega3). The synthesis of long chain fatty acids was noticed to be stimulated, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) recording increased concentrations for experimental group compared to control. In conclusion, the walnut meal supplements positively influenced the nutritional composition of broilers meat (thigh meat) in terms of crude fat deposition and quality of lipids, beneficial for human consumers.